Assessing the upper motor neuron in amyotrophic lateral sclerosis using the triple stimulation technique: A multicenter prospective study. Issue 10 (October 2021) - Grapperon, Aude-Marie; Verschueren, Annie; Jouve, Elisabeth; Morizot-Koutlidis, Régine; Lenglet, Timothée; Pradat, Pierre-François; Salachas, François; Bernard, Emilien; Delstanche, Stéphanie; Maertens de Noordhout, Alain; Guy, Nathalie; Danel, Véronique; et al.
Highlights: - Triple stimulation technique can be used in routine clinical practice and in multicenter studies in ALS patients. - Assessment of corticospinal dysfunction at the first visit of the patient was improved by the use of triple stimulation technique compared to conventional TMS. - Triple stimulation technique results are correlated with the clinical upper motor neuron score and ALSFRS-R. Abstract: Objective: To evaluate the relevance of transcranial magnetic stimulation (TMS) using triple stimulation technique (TST) to assess corticospinal function in amyotrophic lateral sclerosis (ALS) in a large-scale multicenter study. Methods: Six ALS centers performed TST and conventional TMS in upper limbs in 98 ALS patients during their first visit to the center. Clinical evaluation of patients included the revised ALS Functional Rating Scale (ALSFRS-R) and upper motor neuron (UMN) score. Results: TST amplitude ratio was decreased in 62% of patients whereas conventional TMS amplitude ratio was decreased in 25% of patients and central motor conduction time was increased in 16% of patients. TST amplitude ratio was correlated with ALSFRS-R and UMN score. TST amplitude ratio results were not different between the centers. Conclusions: TST is a TMS technique applicable in daily clinical practice in ALS centers for the detection of UMN dysfunction, more sensitive than conventional TMS and related to the clinical condition of the patients. Significance: This multicenter study shows that TST can be a routine clinical tool to evaluate UMN dysfunction at the diagnostic assessment of ALS patients.